Risk assessment methods in occupational health and hygiene: a scoping review. - Floeder, Andrew; Jones, Rachael M; Arnold, Susan F (Annals of Work Exposures & Health, 2025)
Background There are a variety of risk assessment methods to evaluate occupational hazards in the field of industrial hygiene. With the development of emerging technologies in the workforce, the previously established risk assessment methods may need to be adapted or new methods developed to address the risk of new hazards. Methods A scoping review was conducted consistent with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Data was extracted and analyzed using a matrix method before undergoing a narrative synthesis. Risk assessment methods were classified as traditional and nontraditional. Results Seventy-nine articles were included in this scoping review, with 81% using traditional risk assessment methods and 19% using nontraditional methods. Discussion Among the nontraditional methods was control banding, with the most recent applications focused on nanomaterials. This approach, which was borne out of the need for a systematic approach for identifying potential health risks that required the use of engineering controls to be used safely, may have an important role in the area of emerging technologies, where the pace of technological innovation outstrips the rate at which health risks can be assessed and characterized. Risk assessment methods with the capacity to look at groups of similar chemicals and chemical mixtures are needed to address emerging hazards associated with emerging technologies.